Analysis of potentially toxic contaminants in milk powder - Magdalena Mititelu; Lucian Hîncu; Emma Adriana Ozon; Daniela Luiza Baconi; Ioana Paunica; Oana Denisa Bălălău (Journal of Mind and Medical Sciences)
The aim of this study was to identify potentially toxic contaminants in milk powder. Powdered milk contains a range of toxic and non-toxic substances that are present in a wide variety, also having very different origins. A number of seven milk powder samples from different producers sold on the Romanian market were analyzed, the samples that were collected from the original packaging: P1, P 2, P3, P4, P5, P6 and P7. The concentration of the following elements was analyzed using the X-ray (XRF) fluorescence method: potassium (K), chlorine (Cl), calcium (Ca), phosphorus (P) and aluminum (Al). The vast majority of the samples showed the levels of elements K, Ca, Cl, Al, P well above the maximum allowable limit (AML). In a single test, the elements potassium, calcium, chlorine, phosphorus showed levels below the maximum allowable limit, but the level of aluminum was much above. The experimental results showed that the market sells assortments of milk powder that exceed concentrations above the maximum limits established by the legislation in force for some constituent elements. Concentrations of constituent elements are not always specified on food labels, and if this information appears, they are not always the correct values.